Pengaruh Pengetahuan Hijau dan Religiusitas Terhadap Eco-Inovasi Produk Berbahan Baku Etnobotani Lokal - Irawan, Norbertus Citra; Darmaningrum, Kurniawati; Widodo, Zandra Dwanita; Putranto, Reza Ridho; Hanifah, Salma Alya (JURNAL AGROINDUSTRI HALAL, 2024)
This study is driven by the significance of developing herbal medicine using local ethnobotanical ingredients, incorporating green knowledge and religiosity to influence the actions of individual production employees. It investigates the essential role of green knowledge and religiosity in the eco-innovation of herbal medicine from local ethnobotanical sources. Focusing on Solo Raya's herbal medicine agroindustry, the research aims to explore the interplay between green knowledge, religiosity, and product eco-innovation, particularly from the perspective of production employees. Employing a case study and explanatory approach, 100 randomly selected production employees participated, and data were analyzed using structural equation model-partial least squares (SEM-PLS). Results indicate that green knowledge and religiosity significantly contribute to promoting eco-innovation. Green knowledge facilitates the creation of environmentally friendly products with local ethnobotanical materials, while religiosity offers ethical support for sustainable innovation practices. The study underscores the pivotal role of production employees in balancing environmental sustainability and religious values, emphasizing the crucial link between these aspects for advancing eco-innovation in the herbal medicine industry. This research enriches our understanding of eco-innovation dynamics in the agro-industrial sector by embracing green values and religiosity.